THE HISTORICAL ASPECT OF THE ARCHITECTURAL ROAD INFRASTRUCTURE PROTECTION OF UKRAINE (Municipal economy of cities. Series: «Economy science», 2013)
The author has presented the term a modern roadside tourist complex (RTC). The outcomes of the analysis of the Ukrainian architectural environment formation of RTC were illuminated. The timeframes the main stages of the Ukrainian architectural environment PTC formation were identified.